2021
DOI: 10.2147/rmhp.s337287
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Intention of MSM to Use the PrEP Intelligent Reminder System

Abstract: Purpose Low adherence to medication is an important reason why pre-exposure prophylaxis (PrEP) is not effective at reducing the rate of new human immunodeficiency virus (HIV) infections among men who have sex with men (MSM). The intelligent reminder system (IRS) has been designed to improve user compliance, but the intention of MSM to use the IRS remains unclear. This study establishes a theoretical model to analyze the factors influencing their intention to use the IRS. Patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Therefore, MSMs’ behavior for HIV prevention determines whether they will receive medication reminders or information. This finding is consistent with similar studies [ 42 ]. According to the knowledge, attitude, and practice theory, knowledge and attitude are crucial determinants of an individual’s ability to form certain health behaviors [ 52 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, MSMs’ behavior for HIV prevention determines whether they will receive medication reminders or information. This finding is consistent with similar studies [ 42 ]. According to the knowledge, attitude, and practice theory, knowledge and attitude are crucial determinants of an individual’s ability to form certain health behaviors [ 52 ].…”
Section: Discussionsupporting
confidence: 94%
“…The data collection process is shown in Figure 2 . The method of self-administered questionnaire was adopted, and the questionnaires were collected on the spot and checked for completeness and logic [ 42 , 43 ]. Data were obtained in the first follow-up period for the cohort because HBM-related questions were only involved during this period.…”
Section: Methodsmentioning
confidence: 99%
“…PE and SI do not affect the BI, but the role of these two factors could not be ignored in related studies [ 19 , 41 , 42 ], we think the reasons could be as follows: (1) Although HERS can improve the examination efficiency, the improvement is mainly reflected by the data in HIS (comparing the average waiting time before and after using the HERS), and patient’s perception is not obvious; (2) Patients don’t come to the hospital very often. Although HERS has been implemented for six months, some patients are still new to the system; (3) Doctors and patients are still not proficient in using HERS, so they think learning to use HERS will add their troubles, and there are few cases of doctors recommending to patients and patients recommending to patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with a metaregression of studies that evaluated effective clinical decision support using the UTAUT model and suggested that effort expectancy, facilitating conditions, and performance expectancy had a significant impact on clinician behavior [ 42 ]. Numerous studies evaluated medication-related CDS using the UTAUT, including studies examining a comprehensive CDS suite of tools called Sentri7/Quantifi [ 43 ], use of a decision aid for psychotic disorders [ 44 ], medication management in oncology settings [ 45 ], and a tool to help remind HIV positive men to use antiviral therapies when undertaking sexual activities [ 46 ]. However, to our knowledge, none have applied the UTAUT model to DDI-specific SDM.…”
Section: Discussionmentioning
confidence: 99%